Jewellery box inspired by Istana Bandar Alaeddin / Siti Sarah Ahmad Tajalli Alyamany - Ahmad Tajalli Alyamany, Siti Sarah (2022)
The structure, often referred to as lstana Alaeddin or Alaeddin Palace, was made of marble and highquality cengal wood. Mostly of Middle-Eastern and Indian origin, its design is largely Islamic. A jewellery box was created to protect jewellery when it was not being wear. This amazing Malaysian building, which has an unusual geometry structure that makes it look outstanding, served as a major inspiration for this box. This jewellery box got four compartments.